Cobalt-Catalyzed Alkynylation of Organic Compounds: Hydroalkynylation, Dehydrogenative Alkynylation, and Reductive Alkynylation - Ueda, Yohei; Tsurugi, Hayato; Mashima, Kazushi (Synlett, 2023)
Cobalt-catalyzed hydroalkynylation of alkynes, alkenes, and imines affords internal alkynes with various functional groups adjacent to the carbon–carbon triple bond moiety in an atom-economical manner. In addition, cross-coupling of in situ generated alkynylcobalt species from terminal alkynes, haloalkynes, and metal acetylides with (hetero)aromatic compounds and organic halides selectively provides various internal aryl- and alkylalkynes.1 Introduction2 Hydroalkynylation of Alkynes for 1,3-Enyne Synthesis3 Hydroalkynylation of Polar and Nonpolar Double Bonds4 Dehydrogenative Cross-Coupling Reaction Using Terminal Alkynes with Aromatic Compounds5 Cross-Coupling Reactions Using Haloalkynes as the Coupling Partners6 Cross-Coupling Reactions Using Metal Acetylides7 Conclusion
Keywords: cobalt; alkynes; alkynylation; dimerization; haloalkynes; metal acetylides